2015
DOI: 10.1371/journal.pone.0117963
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis of Mitochondrial-Associated ER Membranes (MAM) during RNA Virus Infection Reveals Dynamic Changes in Protein and Organelle Trafficking

Abstract: RIG-I pathway signaling of innate immunity against RNA virus infection is organized between the ER and mitochondria on a subdomain of the ER called the mitochondrial-associated ER membrane (MAM). The RIG-I adaptor protein MAVS transmits downstream signaling of antiviral immunity, with signaling complexes assembling on the MAM in association with mitochondria and peroxisomes. To identify components that regulate MAVS signalosome assembly on the MAM, we characterized the proteome of MAM, ER, and cytosol from cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 92 publications
8
96
0
Order By: Relevance
“…MAMs purification yields the ensemble of membranes that are bound to the ER, including the lipid-MERCs, the ion-MERCs, the phago-MERCs, the ribo-MERCs and the sites where ER tubules contact mitochondria to mediate the Drp-1-dependent constriction that guides mitochondria division, 81,82 the fission-MERC. As such, the current MAM proteomes, 83,84 are representative of the protein collections of all types of MERCs in the tissue and cell type from which the MAMs were isolated. Similarly, localization of major protein complexes like the γ-secretase 30,57 and mTORC2 85 at the MAMs will need to be investigated by immunogold analysis, to associate their localization to a specific MERC thickness and, therefore, function.…”
Section: 80mentioning
confidence: 99%
“…MAMs purification yields the ensemble of membranes that are bound to the ER, including the lipid-MERCs, the ion-MERCs, the phago-MERCs, the ribo-MERCs and the sites where ER tubules contact mitochondria to mediate the Drp-1-dependent constriction that guides mitochondria division, 81,82 the fission-MERC. As such, the current MAM proteomes, 83,84 are representative of the protein collections of all types of MERCs in the tissue and cell type from which the MAMs were isolated. Similarly, localization of major protein complexes like the γ-secretase 30,57 and mTORC2 85 at the MAMs will need to be investigated by immunogold analysis, to associate their localization to a specific MERC thickness and, therefore, function.…”
Section: 80mentioning
confidence: 99%
“…It could regulate the interaction between positive and negative regulators distributed on different organelles in order to fine-tune the RIG-1 induced innate immune response (Horner et al, 2011) (Figure 1). Proteomic analysis of MAM during RNA virus infection revealed an increased presence of peroxisomal proteins if compared to control cells, supporting physical interactions between peroxisomes and mitochondria (or MAM) during antiviral response (Horner et al, 2015).…”
Section: Interplay Between Peroxisomes and Mitochondriamentioning
confidence: 66%
“…This organelle connecting assembly was suggested to act as signaling hub for the regulation of mitochondrial and peroxisomal innate immune responses after viral infection (Horner et al, 2011). In a subsequent publication the authors further reported that the MAM proteome dynamically changes after virus infection in particular increasing the amounts of individual MAVS interacting proteins (Horner et al, 2015). Evaluating their findings, the authors speculated that the MAM may be used to coordinate mitochondrial and peroxisomal metabolism according to the requirements during virus infection.…”
Section: The Mitochondria-associated Membrane Of the Er (Mam)mentioning
confidence: 98%
See 2 more Smart Citations